Coating material for decomposing and adsorbing harmful gas, preparation process and application of coating material as respiratory protection product
By using the combined silver-titanium dioxide and silver nitrate combined with antibacterial materials prepared by combining porous nanotitanium dioxide and silver nitrate, combined with polyurethane and activated carbon, to form a composite coating, the harm of harmful gases to health during smoking and interior decoration is solved, and efficient adsorption and decomposition are achieved Effect.
Patent Information
- Application Number
- CN202411510600.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to effectively reduce the harm of harmful gases generated during smoking and interior decoration to human health, especially the harm of TVOC and bacterial growth to the respiratory tract.
The combined preparation of silver-titanium dioxide and silver nitrate is made of silver-titanium dioxide combined with antibacterial materials, and is carried by polyurethane materials and combined with activated carbon to form a composite coating to adsorb and decompose harmful gases.
It improves the antibacterial and anti-pollution ability of the coating materials, enhances the adsorption and degradation effect of TVOC and particulate matter, and effectively reduces the harm to human health.
Smart Images

Figure CN119386841A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of harmful gas adsorption, and in particular to a coating material for decomposing and adsorbing harmful gases, a preparation process and an application as a respiratory protection product. Background Art
[0002] Nowadays, smoking is a normal thing. Smoking will cause direct harm to smokers, and a large amount of secondhand smoke will be produced during the smoking process, which is also very harmful to the human body. Not only cigarettes, but also the gases produced by modern interior decoration, such as painting, will also cause a lot of harm to the human body.
[0003] The main harmful substances produced by the above pollution sources include a large amount of TVOC and PM2.5, which are also accompanied by the growth of bacteria, causing great harm to the human respiratory tract. In response to the problems raised in the above background technology, we propose an antibacterial material that can be applied to the filter of cigarettes or attached to the surface of furniture to effectively reduce the harm of TVOC and bacterial growth to human health. Summary of the invention
[0004] The purpose of the present invention is to provide a coating material for decomposing and adsorbing harmful gases, a preparation process and an application as a respiratory protection product, so as to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A preparation process of a coating material for decomposing and adsorbing harmful gases, comprising the following steps:
[0007] S1. Ultrasonic dispersion of porous nano-titanium dioxide into a mixed solution of ethanol and water in a mass ratio of 1:1 forms a porous nano-titanium dioxide solution, and a silver nitrate solution with a mass fraction of 0.5-2wt% is added dropwise to the porous nano-titanium dioxide solution. The mixture is stirred for reaction for 1.5-2h and then dried in an oven at 70-85°C. The dried product is washed with deionized water and then placed in a muffle furnace and calcined at 350-500°C for 1-2h to obtain a silver-titanium dioxide combined antibacterial material.
[0008] S2, dissolving the first polyurethane particles in DMF solvent, ultrasonically dispersing the silver-titanium dioxide combined antibacterial material prepared in step S1 into the above DMF solvent and adding a pore expander, stirring for 1-2 hours until the mixture is uniform, standing to defoam, casting on a template to form a film, and drying in an oven at 90-110° C. to remove the solvent, to obtain a first polyurethane film;
[0009] S3, dissolving the second polyurethane particles in DMF solvent, dispersing activated carbon particles with a particle size of 100-200 mesh in the above DMF solvent and adding a pore expander, stirring for 1-2 hours until the mixture is uniform, standing to defoam, casting on a template to form a film, and drying in an oven at 90-110° C. to remove the solvent, to obtain a second polyurethane film;
[0010] S4. Spray an acrylic adhesive onto the surface of the first polyurethane film prepared in step S2, cover the second polyurethane film prepared in step S3 on the first polyurethane film, and apply a pressure of 0.1-0.3 MPA to obtain a coating that decomposes and absorbs harmful gases.
[0011] Furthermore, in step S1, the mass ratio of the porous nano-titanium dioxide to the mixed solution is 1:30-1:50, and the mass ratio of the silver nitrate solution to the mixed solution is 1:1-1:2.
[0012] Furthermore, in step S2, the mass ratio of the silver-titanium dioxide combined antibacterial material, the pore expanding agent, the first polyurethane particles and the DMF solvent is 1:(1-3):(5-8):(25-40).
[0013] Furthermore, in the step S3, the mass ratio of the activated carbon, the pore expanding agent, the second polyurethane particles and the DMF solvent is 1:(0.8-1.4):(5-8):(25-40), the first polyurethane particles in the step S2 and the second polyurethane particles in the step S3 are polyester polyurethane particles or polyether polyurethane particles, and the pore expanding agent in the step S2 and the step S3 is chitin or sodium chloride.
[0014] Furthermore, the porous nano-titanium dioxide in step S1 is prepared by the following method:
[0015] S101, dispersing titanic acid in 30wt% hydrogen peroxide, adding chitosan, stirring evenly, dropping 25wt% ammonia water into the above solution, stirring and mixing for 0.8-2h to obtain a mixed sol;
[0016] S102, placing the mixed sol obtained in step S101 into an oven at 100-120°C for drying, placing the dried product into a muffle furnace and calcining it at 600-800°C for 2-3h to obtain porous nano-titanium dioxide.
[0017] Furthermore, the mass ratio of chitosan, titanic acid, hydrogen peroxide and ammonia water is 1:(3-5):(24-32):(8-12).
[0018] A coating material for decomposing and absorbing harmful gases is prepared by the above-mentioned preparation process of a coating material for decomposing and absorbing harmful gases.
[0019] A coating material for decomposing and adsorbing harmful gases is used as a respiratory protection product.
[0020] Furthermore, the coating material is applied to the filter tip of a cigarette.
[0021] Furthermore, the coating material is applied to a coating material on the surface of furniture.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention adopts porous nano-titanium dioxide and silver nitrate to prepare the silver-titanium dioxide combined antibacterial material. The titanium dioxide prepared with chitosan as the biological template has a porous characteristic. The porous characteristic can not only improve its contact with bacteria, TVOC and particulate matter, and improve the antibacterial ability, but also can more evenly adsorb silver ions, further improve the antibacterial and anti-pollution ability of the coating material. The combined antibacterial material is carried by the polyurethane material, and the silver ions are not easy to be separated from the polyurethane surface, which is convenient for removing organic matter and bacteria. The polyurethane material in the present invention is also adsorbed with activated carbon, which increases the surface area and improves the adsorption effect;
[0024] 2. The composite coating prepared by the present invention is composed of a double layer of polyurethane material, and the silver-titanium dioxide combined antibacterial material and activated carbon are respectively located in different polyurethane material layers, allowing more target substance molecules to contact and adsorb to the surface, thereby improving the overall adsorption capacity and efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] See also Figure 1 , the present invention provides:
[0028] Example 1
[0029] A preparation process of a coating material for decomposing and adsorbing harmful gases, comprising the following steps:
[0030] Preparation of porous nano-titanium dioxide:
[0031] S101, dispersing 25g of metatitanic acid in 160g of 30wt% hydrogen peroxide, adding 5g of chitosan, stirring evenly, dropping 60g of 25wt% ammonia water into the above solution, stirring and mixing for 2h to obtain a mixed sol;
[0032] S102, placing the mixed sol obtained in step S101 into an oven at 120° C. for drying, placing the dried product into a muffle furnace and calcining it at 800° C. for 2 h to obtain porous nano-titanium dioxide;
[0033] S1. Ultrasonic dispersion of 15 g of porous nano-titanium dioxide into 750 g of a mixed solution of ethanol and water in a mass ratio of 1:1 forms a porous nano-titanium dioxide solution, and dropwise addition of 375 g of a silver nitrate solution with a mass fraction of 2 wt % into the porous nano-titanium dioxide solution. The mixture is stirred for reaction for 2 h and then dried in an oven at 85° C. The dried product is washed with deionized water and then placed in a muffle furnace and calcined at 500° C. for 1 h to obtain a silver-titanium dioxide combined antibacterial material.
[0034] S2, dissolving 80g of polyester polyurethane particles in 400g of DMF solvent, dispersing 10g of the silver-titanium dioxide combined antibacterial material prepared in step S1 into the above DMF solvent by ultrasonic, adding 30g of chitin, stirring for 2h until the mixture is uniform, standing to defoam, casting on a template to form a film, and drying in an oven at 110°C to remove the solvent to obtain a first polyurethane film;
[0035] S3, dissolving 80g of polyester polyurethane particles in 400g of DMF solvent, dispersing 10g of activated carbon particles with a particle size of 100 meshes into the above DMF solvent and adding 14g of chitosan, stirring for 2h until the mixture is uniform, standing to defoam, casting on a template to form a film, and drying in an oven at 110°C to remove the solvent to obtain a second polyurethane film;
[0036] S4. Spray an acrylic adhesive onto the surface of the first polyurethane film prepared in step S2, cover the second polyurethane film prepared in step S3 on the first polyurethane film, and apply a pressure of 0.3 MPA to obtain a coating that decomposes and absorbs harmful gases.
[0037] Example 2
[0038] A preparation process of a coating material for decomposing and adsorbing harmful gases, comprising the following steps:
[0039] Preparation of porous nano-titanium dioxide:
[0040] S101, dispersing 15 g of metatitanic acid in 120 g of 30 wt% hydrogen peroxide, adding 5 g of chitosan, stirring evenly, dropping 40 g of 25 wt% ammonia water into the above solution, stirring and mixing for 0.8 h to obtain a mixed sol;
[0041] S102, placing the mixed sol obtained in step S101 into an oven at 100° C. for drying, placing the dried product into a muffle furnace and calcining it at 600° C. for 3 h to obtain porous nano-titanium dioxide;
[0042] S1. Ultrasonic dispersion of 15 g of porous nano-titanium dioxide into 450 g of a mixed solution of ethanol and water in a mass ratio of 1:1 forms a porous nano-titanium dioxide solution, and dropwise addition of 450 g of a silver nitrate solution with a mass fraction of 0.5 wt % into the porous nano-titanium dioxide solution. The mixture is stirred for reaction for 1.5 h and then dried in an oven at 85° C. The dried product is washed with deionized water and then placed in a muffle furnace and calcined at 350° C. for 2 h to obtain a silver-titanium dioxide combined antibacterial material.
[0043] S2, dissolving 50g of polyether polyurethane particles in 250g of DMF solvent, ultrasonically dispersing 10g of the silver-titanium dioxide combined antibacterial material prepared in step S1 into the above DMF solvent and adding 10g of sodium chloride, stirring for 1h until the mixture is uniform, standing to defoam, casting on a template to form a film, and drying in an oven at 90°C to remove the solvent to obtain a first polyurethane film;
[0044] S3, dissolving 50g of polyether polyurethane particles in 250g of DMF solvent, dispersing activated carbon particles with a particle size of 200 meshes into the above DMF solvent and adding 8g of sodium chloride, stirring for 1h until the mixture is uniform, standing to defoam, casting on a template to form a film, and drying in an oven at 90°C to remove the solvent to obtain a second polyurethane film;
[0045] S4. Spray an acrylic adhesive onto the surface of the first polyurethane film prepared in step S2, cover the second polyurethane film prepared in step S3 on the first polyurethane film, and apply a pressure of 0.1 MPA to obtain a coating that decomposes and absorbs harmful gases.
[0046] Example 3
[0047] A preparation process of a coating material for decomposing and adsorbing harmful gases, comprising the following steps:
[0048] Preparation of porous nano-titanium dioxide:
[0049] S101, dispersing 20g of metatitanic acid in 150g of 30wt% hydrogen peroxide, adding 5g of chitosan, stirring evenly, dropping 50g of 25wt% ammonia water into the above solution, stirring and mixing for 1.2h to obtain a mixed sol;
[0050] S102, placing the mixed sol obtained in step S101 into an oven at 105° C. for drying, placing the dried product into a muffle furnace and calcining it at 750° C. for 2.8 h to obtain porous nano-titanium dioxide;
[0051] S1. Ultrasonic dispersion of 15 g of porous nano-titanium dioxide into 580 g of a mixed solution of ethanol and water in a mass ratio of 1:1 forms a porous nano-titanium dioxide solution, and dropwise addition of 490 g of a silver nitrate solution with a mass fraction of 1.5 wt % into the porous nano-titanium dioxide solution. The mixture is stirred for reaction for 1.8 h and then dried in an oven at 70° C. The dried product is washed with deionized water and then placed in a muffle furnace and calcined at 500° C. for 2 h to obtain a silver-titanium dioxide combined antibacterial material.
[0052] S2, dissolving 70g of polyether polyurethane particles in 350g of DMF solvent, dispersing 10g of silver-titanium dioxide combined antibacterial material prepared in step S1 into the above DMF solvent by ultrasonic, adding 25g of chitin, stirring for 1.5h until the mixture is uniform, standing to defoam, casting on a template to form a film, and drying in an oven at 110°C to remove the solvent to obtain a first polyurethane film;
[0053] S3, dissolving 68g of the second polyurethane particles in 330g of DMF solvent, dispersing 10g of activated carbon particles with a particle size of 160 meshes into the above DMF solvent and adding 10g of chitosan, stirring for 1.5h until the mixture is uniform, standing to defoam, casting on a template to form a film, and drying in an oven at 100°C to remove the solvent to obtain a second polyurethane film;
[0054] S4. Spray an acrylic adhesive onto the surface of the first polyurethane film prepared in step S2, cover the second polyurethane film prepared in step S3 on the first polyurethane film, and apply a pressure of 0.2 MPA to obtain a coating that decomposes and absorbs harmful gases.
[0055] Comparative Example 1
[0056] The difference between Comparative Example 1 and Example 1 is that step S101 and step S102 are completely eliminated, and ordinary nano titanium dioxide is directly added in step S1 instead. The remaining steps are exactly the same as those in Example 1.
[0057] Comparative Example 2
[0058] The difference between Comparative Example 2 and Example 1 is that step S1 is completely eliminated, and porous titanium dioxide is directly added to step S2 instead. The remaining steps are exactly the same as those in Example 1.
[0059] Comparative Example 3
[0060] The difference between Comparative Example 3 and Comparative Example 1 is that step S1 is completely eliminated, and ordinary nano titanium dioxide is directly added to step S2 instead. The remaining steps are exactly the same as those in Example 1.
[0061] The coating materials prepared in the above Examples 1-4 and Comparative Examples 1-3 were tested for their antibacterial properties against Staphylococcus aureus. The test method was to culture the inoculated bacterial solution of Staphylococcus aureus. The total number of colonies in the initial bacterial solution was 1.0×10 4 cfu / cm 2 , respectively select the coating materials prepared in Examples 1-4 and Comparative Examples 1-3 as samples, and elute with an eluent (the eluent is a phosphate saline eluent) after culturing for 24 hours, and calculate the viable bacteria count and antibacterial rate of the eluent according to the national standard GB4789.2. The test results are shown in Table 1 below;
[0062] Table 1: Antibacterial test table of the coating materials prepared in Examples 1-4 and Comparative Examples 1-3 against Staphylococcus aureus
[0063]
[0064] It can be seen from the data between Example 1 and Comparative Example 1 in Table 1 above that the present invention can better compound with silver ions by using porous titanium dioxide, thereby improving the antibacterial ability of the product; it can be seen from the comparison of the data between Comparative Example 2 and Comparative Example 3 that after the porous nano titanium dioxide is prepared, the present invention has more holes on its surface, which can also further improve the antibacterial ability of the coating material;
[0065] The coating materials prepared in the above Examples 1-4 and Comparative Examples 1-3 were respectively prepared into filter tips to simulate the filtering effect of cigarette holders. Particulate matter PM2.5, formaldehyde and resorcinol were selected for simulation experiments. The concentrations of each pollutant at the air inlet end (before filtration) and the air outlet end (after filtration) were tested respectively, and the data in Table 2 below were obtained:
[0066] Table 2: Filtration test table of PM2.5, formaldehyde and resorcinol of coating material particles prepared in Examples 1-4 and Comparative Examples 1-3
[0067]
[0068]
[0069] The initial concentrations of PM2.5, formaldehyde and resorcinol before filtration were 250ug / m 3 , 1.46mg / m 3 and 1.58 mg / m3. It can be seen from the data of Example 1 and Comparative Example 1 that the present invention has an obvious improvement in the filtering effect on PM2.5, formaldehyde and resorcinol in the air after using porous titanium dioxide. This is because the titanium dioxide in a porous state is easier to contact with the pollutants above, thereby achieving the purpose of adsorption and degradation.
[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A process for preparing a coating material for decomposing and adsorbing harmful gases, characterized in that: The steps include: S1. Ultrasonic dispersion of porous nano-titanium dioxide into a mixed solution of ethanol and water in a mass ratio of 1:1 forms a porous nano-titanium dioxide solution, and a silver nitrate solution with a mass fraction of 0.5-2wt% is added dropwise to the porous nano-titanium dioxide solution. The mixture is stirred for reaction for 1.5-2h and then dried in an oven at 70-85°C. The dried product is washed with deionized water and then placed in a muffle furnace and calcined at 350-500°C for 1-2h to obtain a silver-titanium dioxide combined antibacterial material. S2, dissolving the first polyurethane particles in DMF solvent, ultrasonically dispersing the silver-titanium dioxide combined antibacterial material prepared in step S1 into the above DMF solvent and adding a pore expander, stirring for 1-2 hours until the mixture is uniform, standing to defoam, casting on a template to form a film, and drying in an oven at 90-110° C. to remove the solvent, to obtain a first polyurethane film; S3, dissolving the second polyurethane particles in DMF solvent, dispersing activated carbon particles with a particle size of 100-200 mesh in the above DMF solvent and adding a pore expander, stirring for 1-2 hours until the mixture is uniform, standing to defoam, casting on a template to form a film, and drying in an oven at 90-110° C. to remove the solvent, to obtain a second polyurethane film; S4. Spray an acrylic adhesive onto the surface of the first polyurethane film prepared in step S2, cover the second polyurethane film prepared in step S3 on the first polyurethane film, and apply a pressure of 0.1-0.3 MPA to obtain a coating that decomposes and absorbs harmful gases.
2. The preparation process of a coating material for decomposing and adsorbing harmful gases according to claim 1, characterized in that: In the step S1, the mass ratio of the porous nano-titanium dioxide to the mixed solution is 1:30-1:50, and the mass ratio of the silver nitrate solution to the mixed solution is 1:1-1:
2.
3. The process for preparing a coating material for decomposing and adsorbing harmful gases according to claim 1, characterized in that: In the step S2, the mass ratio of the silver-titanium dioxide combined antibacterial material, the pore expander, the first polyurethane particles and the DMF solvent is 1:(1-3):(5-8):(25-40).
4. The process for preparing a coating material for decomposing and adsorbing harmful gases according to claim 1, characterized in that: The mass ratio of the activated carbon, the pore expanding agent, the second polyurethane particles and the DMF solvent in the step S3 is 1:(0.8-1.4):(5-8):(25-40), the first polyurethane particles in the step S2 and the second polyurethane particles in the step S3 are polyester polyurethane particles or polyether polyurethane particles, and the pore expanding agent in the step S2 and the step S3 is chitin or sodium chloride.
5. The process for preparing a coating material for decomposing and adsorbing harmful gases according to claim 1, characterized in that: The porous nano-titanium dioxide in step S1 is prepared by the following method: S101, dispersing titanic acid in 30wt% hydrogen peroxide, adding chitosan, stirring evenly, dropping 25wt% ammonia water into the above solution, stirring and mixing for 0.8-2h to obtain a mixed sol; S102, placing the mixed sol obtained in step S101 into an oven at 100-120°C for drying, placing the dried product into a muffle furnace and calcining it at 600-800°C for 2-3h to obtain porous nano-titanium dioxide.
6. The process for preparing a coating material for decomposing and adsorbing harmful gases according to claim 5, characterized in that: The mass ratio of chitosan, titanic acid, hydrogen peroxide and ammonia water is 1:(3-5):(24-32):(8-12).
7. A coating material for decomposing and adsorbing harmful gases, characterized in that: The coating material is prepared by the preparation process for decomposing and adsorbing harmful gases as described in any one of claims 1 to 6.
8. Use of the coating material for decomposing and adsorbing harmful gases according to claim 7 as a respiratory protection product.
9. The use of a coating material for decomposing and adsorbing harmful gases as a respiratory protection product according to claim 8, characterized in that: The coating material is used in the production of cigarettes.
10. The use of the coating material for decomposing and adsorbing harmful gases as a respiratory protection product according to claim 9, characterized in that: The coating material is used in the production of furniture.